Intertidal diatom communities reflect patchiness in groundwater discharge. (20th September 2015) - Welti, N.; Gale, D.; Hayes, M.; Kumar, A.; Gasparon, M.; Gibbes, B.; Lockington, D.
Abstract: We report on two discrete intertidal springs which discharge freshwater into Moreton Bay, Australia. Results from a seven month field survey which monitored chemical and hydraulic parameters, indicate fresh groundwater is continuously discharged from these features. Porewater measured from both groundwater springs (GWS) had consistently low salinity (0.07 ± 0.04 psu), pH (5) and high oxidation reduction potential (ORP; 194 mV) relative to the adjacent intertidal area (27.8 ± 16.7 psu; 6.8 pH; −92.3 ± 123.2 mV). Positive ORP, which suggests high dissolved oxygen, combined with lower concentrations of ammonium (N–NH4 + ) and higher concentrations of nitrate (N–NO3 − ) relative to the intertidal area, reveal that these sites transport and cycle nutrients differently than the surrounding beach. The C:N:P ratio from the GWS sites differs significantly ( p < 0.05) from the rest of the intertidal zone, with lower C:N and higher N:P ratios measured from the GWS relative to the rest of the intertidal zone. The unique geochemical characteristics of the GWS sites appear to influence the abundance and species assemblage of the local phytoplankton community. Diatom assemblages from the two GWS were taxonomically distinct to the diatom assemblage of the surrounding intertidal zone. A total of 25 taxa were identified within the entire field area. Of these, four were unique to freshwater habitats and found only at the GWS. Based on the differences in nutrient and geochemical composition between the GWS sites and the adjacent intertidal porewater, two scenarios explaining the source of the GWS are further hypothesized. This study emphasizes the importance of considering small-scale heterogeneous submarine groundwater discharge (SGD) for local nutrient budgets and subsequent impacts on local biota.